Differential tissue expression of extracellular vesicle‐derived proteins in prostate cancer. Issue 9 (24th April 2019) - Duijvesz, Diederick; Rodriguez‐Blanco, Giovanny; Hoogland, A. Marije; Verhoef, Esther I.; Dekker, Lennard J.; Roobol, Monique J.; van Leenders, Geert J. L. H.; Luider, Theo M.; Jenster, Guido
Abstract: Background: Proteomic profiling of extracellular vesicles (EVs) from prostate cancer (PCa) and normal prostate cell lines, led to the identification of new candidate PCa markers. These proteins included the nuclear exportin proteins XPO1 (also known as CRM1), the EV‐associated PDCD6IP (also known as ALIX), and the previously published fatty acid synthase FASN. In this study, we investigated differences in expression of XPO1 and PDCD6IP on well‐characterized prostate cancer cohorts using mass spectrometry and tissue microarray (TMA) immunohistochemistry to determine their diagnostic and prognostic value. Methods: Protein fractions from 67 tissue samples (n = 33 normal adjacent prostate [NAP] and n = 34 PCa) were analyzed by mass spectrometry (nano‐LC‐MS‐MS). Label‐free quantification of EVs was performed to identify differentially expressed proteins between PCa and NAP. Prognostic evaluation of the candidate markers was performed with a TMA, containing 481 radical prostatectomy samples. Samples were stained for the candidate markers and correlated with patient information and clinicopathological outcome. Results: XPO1 was higher expressed in PCa compared to NAP in the MS data analysis ( P > 0.0001). PDCD6IP was not significantly higher expressed ( P = 0.0501). High cytoplasmic XPO1 staining in the TMA immunohistochemistry, correlated in a multivariable model with high Gleason scores ( P = 0.002) and PCa‐related death ( P = 0.009). Conclusion: High expression of cytoplasmic XPO1 shows correlation with prostate cancer and has added clinical value in tissue samples. Furthermore, as an extracellular vesicles‐associated protein, it might be a novel relevant liquid biomarker.